Male college students' experiences of depressive and anxiety-related symptoms and help-seeking processes: a qualitative study - Gültüter, Abdullah Cankut (İstanbul Bilgi Üniversitesi, Lisansüstü Eğitim Enstitüsü)
College students are in a transitional period related to emerging adulthood in which they deal with different dimensions of life, and this period might create distress and worry in them. Research shows that, in this period, they tend to suffer from mental health problems, especially depressive and anxiety-related ones. To handle their problems, they utilize different coping strategies and help-seeking behavior. Considering previous research, male college students have different tendencies, strategies, and needs in terms of their mental health problems, coping ways, and help-seeking behavior. From the perspective of hegemonic masculinity, the literature showed different impacts of masculinity norms on men’s mental health, as well as their coping and help-seeking processes. With the purpose of examining male college students’ experiences of mental health problems, the current study investigated their depressive and anxiety-related experiences and how their ideas and perceptions of masculinity norms shaped their experiences in Türkiye. In addition, in light of the ecological perspective, the current study examined the experiences of participants in both micro (e.g., friends, partners, and family) and macro (e.g., Türkiye) contexts. The current study used a qualitative design, and eight male college students suffering from depressive and anxiety-related symptoms were recruited. In semi-structured individual interviews, participants’ mental health experiences, their coping ways, help-seeking behavior, and masculinity ideas were explored in different contexts. The interviews were analyzed through thematic analysis in the MAXQDA 2024 Software Program. Five themes were specified as “expression of symptoms,” “barriers to disclosure,” “masculinity norms about mental health,” “coping with symptoms,” and “feeling supported,” and they were explained through the accounts of participants. Besides, how masculinity norms shaped the experiences of male college students was discussed, considering their contextual experiences. Finally, practice implications, strengths, and limitations of the current study were discussed, and suggestions for future research were explained.